Study on extract-pyrolysis cascading utilization characteristics of typical biomass using imidazolium-based ionic liquids. (15th August 2023) - Jiao, Tiantian; Lin, Shaojie; Bai, Guangming; Ren, Chuhan; Zhang, Yaqing; Li, Xiangping; Zhang, Huawei; Liang, Peng
Graphical abstract: Highlights: Extract-pyrolysis cascading utilization approach was applied in CH and PS. The extraction yield of CH was higher than PS, BmimCl obtained highest extraction yield. ILs exhibited strong extraction abilities for oxygen and nitrogen containing compounds. Products composition and distribution can be improved via extraction-pyrolysis process. Differentiated extract-pyrolysis characteristics were exhibited for PS and CH. Abstract: As the main utilization method of biomass, direct pyrolysis destroyed high value-added constituents. Extract-pyrolysis cascading utilization technical was applied in two typical biomasses: chlorella (CH) and pine sawdust (PS). Four imidazolium-based ionic liquids (ILs) were chosen as the extractants, and obtained higher extraction yield for CH than PS. Among them, BmimCl (1-Butyl-3-methylimidazolium chloride) obtained highest extraction yield for CH and PS of 72.73% and 20.58%. Selected ILs exhibited strong extraction abilities of oxygen-containing compounds for both CH and PS and nitrogen-containing compounds for CH. Compared with direct pyrolysis, gas and char yields of CH and PS had obvious decrease and the liquid phase products yields increased with more diverse composition especially phenolic compounds. The liquid phase products yield of PS and CH increased by 27.15%, 37.80% and 61.20%, 70.82% using BmimHSO4 (1-Butyl-3-methylimidazolium hydrogensulfate) and BmimCl. The extract-pyrolysis characteristics of CH and PS were obtained through the comparison of gas–liquid-solid products composition and distribution, and they depend on the structure of biomass and the physical–chemical properties of ILs. Extract-pyrolysis utilization approach has potential to realize clean and high-value utilization of biomass, and more valuable liquid products can be obtained.